Plasmablastic extramedullary plasmacytoma - Irulandy Ponniah; Suhasini Rajan (Wolters Kluwer Medknow Publications, 2012)
Extramedullary plasmactyoma is the solitary, soft tissue form of plasma cell neoplasm but lack the defining features of medullary or multiple myeloma. The diagnosis is difficult to make in routine practice setting due to the morphological and immunohistochemical overlap with plasmablastic lymphoma. We report a case of plasmablastic extramedullary plasmacytoma in a 52-year-old in the mandibular lingual gingiva and discuss its differential from plasmablastic lymphoma. The gingival mass regressed with primary radiotherapy.